Optimizing Corporate Financial Decision Making Through Strategic Management Accounting - Made Susilawati; Hari Setia Putra (Pt. Anagata Sembagi Education, 2025)
This study aims to examine and analyze the extent to which the implementation of strategic management accounting can optimize corporate financial decision-making. In an increasingly competitive and complex business environment, accurate and data-driven decision-making has become a crucial need for every organization. In this study, strategic management accounting is formulated through three main variables: Strategic Planning, Value Chain Analysis, and the Balanced Scorecard. This research adopts a quantitative approach using the Partial Least Squares Structural Equation Modeling (PLS-SEM) analysis technique, conducted through the SmartPLS software. The study involved 109 respondents consisting of financial managers and accounting staff from various companies. The results indicate that all three variables have a positive and significant influence on financial decision-making, with the Balanced Scorecard emerging as the most dominant variable. These findings emphasize the importance of applying a strategic framework in management accounting to improve the quality of financial information, operational efficiency, and accuracy in formulating financial policies. This research provides practical contributions for company management in adopting strategic management accounting-based financial decision-making strategies comprehensively and sustainably.